Oddziaływanie finansów publicznych na redystrybucję dochodów w sektorze rolniczych gospodarstw domowych - Leszczyńska, Małgorzata (The Influence of Public Finances on Income Redistribution Among Sector of Rural Households, 2009)
Income status of rural sector is set, on the one hand, by mechanism of market economy and, on the other hand, by transfers, which are outflows and inflows. In the paper, the attention is paid especially to proportions of flow of transfers that is created by state budget within mechanism of secondary redistribution of incomes in time. Although structural instruments supporting non-rural functions and development of rural areas will gain more and more importance because of progressive integration, instruments of social policy are still too excessively used in the Polish system of public finances. The Polish mechanism of redistribution orientated in such a way can decrease income differences in a short term, however, it cannot lead to the desired processes of enhancing efficiency in rural sector in a long term. That is why, the income policy - directed mainly at supporting structural changes should be separated from the social policy
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 150-158